Quantitative PCR for human herpesviruses 6 and 7. - Secchiero, P (1995)
A quantitative PCR assay for the detection of human herpesvirus 6 (HHV-6) (variants A and B) and HHV-7 DNAs in clinical samples was developed. The assay uses a nonhomologous internal standard (IS) for each virus that is coamplified with the wild-type target sequence in the same vial and with the same pair of primers. This method allows for a correction of the variability of efficiency of the PCR technique. A standard curve is constructed for each experiment by coamplification of known quantities of the cloned HHV-6 or HHV-7 target templates with the respective IS. Absolute quantitation of the test samples is then achieved by determining the viral target/IS ratio of the hybridization signals of the amplification products and plotting this value against the standard curve. Using this assay, we quantitated the amount of HHV-6 or HHV-7 DNA in infected cell cultures and demonstrated an inhibitory effect of phosphonoformic acid on the replication of HHV-6 and HHV-7 in vitro. As the first clinical application of this procedure, we performed preliminary measurements of the loads of HHV-6 and HHV-7 in lymph nodes from patients with Hodgkin's disease and AIDS. Application of this quantitative PCR method should be helpful for elucidating the pathogenic roles of HHV-6 and HHV-7.